What constitutes a neglected tropical disease? - Hotez, Peter J.; Aksoy, Serap; Brindley, Paul J.; Kamhawi, Shaden (PLOS Neglected Tropical Diseases, 2020)
The World Health Organization (WHO) currently classifies 20 diseases and conditions as neglected tropical diseases (NTDs). However, since its inception in 2007, PLOS Neglected Tropical Diseases has considered an expanded list that includes additional diseases with the chronic and/or debilitating, and poverty-promoting features of NTDs. Described here is an update of our current scope, which attempts to embrace all of the NTDs, and a discussion of the status of some of the more debated medical conditions in terms of whether or not they constitute an NTD.